Pengaruh Times Interest Earned Ratio Dan Total Asset Turnover Terhadap Return On Asset Pada PT Mayora, Tbk - Tri Sudryanto; Nurul Huda (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This research aims to measure the influence of Times Interest Earned Ratio and Total Asset Turnover on Return on Assets at PT Mayora, Tbk. The research sample consisted of 11 financial reports starting from 2011-2021. The type of data is quantitative, while the data source is secondary. Documentation data collection method, which is obtained by downloading financial reports via www.idx.co.id/id. Quantitative descriptive data analysis method with statistical analysis tools. Analysis includes classic assumption tests, multiple liner analysis, correlation coefficient, coefficient of determination, t test and f test. The results of the research state that the Times Interest Earned Ratio variable has an influence on Return on Assets (ROA), the Total Asset Turnover variable has no influence on Return on Assets (ROA), the Times Interest Earned Ratio and Total Asset Turnover simultaneously have a significant effect on Return on Assets in PT. Mayora Indah Tbk. The ability of the independent variable to explain changes in the dependent variable is shown by an Adjusted Square value of 53.1%.